Structure of nanocrystalline MgFe2O4 from X-ray diffraction, Rietveld and atomic pair distribution function analysis - Gateshki, Milen; Petkov, Valeri; Pradhan, Swapan K.; Vogt, Tom (Journal of applied crystallography, 2005)
The three‐dimensional structure of nanocrystalline magnesium ferrite, MgFe2O4, prepared by ball milling, has been determined using synchrotron radiation powder diffraction and employing both Rietveld and atomic pair distribution function (PDF) analysis. The nanocrystalline ferrite exhibits a very limited structural coherence length and a high degree of structural disorder. Nevertheless, the nanoferrite possesses a very well defined local atomic ordering that may be described in terms of a spinel‐type structure with Mg2+ and Fe3+ ions almost randomly distributed over its tetrahedral and octahedral sites. The new structural information helps explain the material's unusual magnetic properties.